2012
DOI: 10.1101/gad.194027.112
|View full text |Cite
|
Sign up to set email alerts
|

Merlin/ERM proteins establish cortical asymmetry and centrosome position

Abstract: The ability to generate asymmetry at the cell cortex underlies cell polarization and asymmetric cell division. Here we demonstrate a novel role for the tumor suppressor Merlin and closely related ERM proteins (Ezrin, Radixin, and Moesin) in generating cortical asymmetry in the absence of external cues. Our data reveal that Merlin functions to restrict the cortical distribution of the actin regulator Ezrin, which in turn positions the interphase centrosome in single epithelial cells and three-dimensional organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(113 citation statements)
references
References 67 publications
9
104
0
Order By: Relevance
“…Mitotic spindle orientation largely relies on astral microtubules and cortical actin cytoskeleton 15,16 . We hypothesized that extracellular signals known to regulate actin and microtubule dynamics, such as axon guidance cues, could be good candidates to influence cell division orientation.…”
Section: Apicobasal Orientation Of Progenitor Division Is Stereotypedmentioning
confidence: 99%
“…Mitotic spindle orientation largely relies on astral microtubules and cortical actin cytoskeleton 15,16 . We hypothesized that extracellular signals known to regulate actin and microtubule dynamics, such as axon guidance cues, could be good candidates to influence cell division orientation.…”
Section: Apicobasal Orientation Of Progenitor Division Is Stereotypedmentioning
confidence: 99%
“…Cortical ezrin also undergoes a dynamic cell cycle-dependent redistribution in mammalian colonic epithelial (Caco2) cells; studies of this phenomenon uncovered a direct role for ezrin in orienting the centrosome and mitotic spindle (Hebert et al, 2012). When embedded in Matrigel, individual Caco2 cells undergo a well-studied program of polarized cyst formation (Jaffe et al, 2008).…”
Section: Controlling the Mechanical Properties Of The Cell Cortexmentioning
confidence: 99%
“…When embedded in Matrigel, individual Caco2 cells undergo a well-studied program of polarized cyst formation (Jaffe et al, 2008). Recent studies have revealed that in single embedded Caco2 cells, ezrin is progressively restricted from a uniform cortical distribution into a discrete actin-rich cap-like structure in the absence of external spatial cues (Hebert et al, 2012). The ezrin 'cap' forms just prior to S phase and instructively positions the interphase centrosome and one pole of the ensuing mitotic spindle, likely providing a stiff platform for astral microtubule attachment.…”
Section: Controlling the Mechanical Properties Of The Cell Cortexmentioning
confidence: 99%
See 2 more Smart Citations